Novel Etiological and Therapeutic Strategies for Neurodiseases: Epigenetic Understanding of Gene–Environment Interactions - Takeo Kubota; Kunio Miyake; Takae Hirasawa; Kaoru Nagai; Tsuyoshi Koide (Journal of Pharmacological Sciences, 2010)
Epigenetics is a mechanism that regulates gene expression not depending on the underlying DNA sequence, but on the chemical modifications of DNA and histone proteins. Defects in the factors involved in epigenetic regulation cause congenital neurodevelopmental diseases, and thus, epigenetic regulation is essential for normal brain development. Besides these intrinsic defects, it is becoming increasingly apparent that extrinsic factors, such as insufficient nutrition, psychiatric drugs, and mental stress, also alter epigenetic regulation. Therefore, environmental factors may lead to “acquired” neurodevelopmental disorders through the failure of epigenetic regulation. Epigenetics is a biological key to understand the gene–environment interactions in neurodevelopmental disorders. As the mechanism is reversible, its comprehensive understanding will result in the development of new therapies for these disorders. Keywords:: epigenetics, DNA methylation, brain, environment, neurodevelopmental disorder, neurodisease